Eksplorasi Sosial dalam Seni: Proses Kreatif Komunitas FORMMISI-YK di ISI Yogyakarta - Tania, Geminisya Aldheana (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
The ability and the same vision of each member spurs the growth of the arts space which can become a new platform and means of self-actualization. Communities can be the forerunner to the birth of creative and innovative human resources. The Formmisi-Yk community in ISI Yogyakarta is a model for creating creative people. How Formmisi-Yk maintains their creative process is a question that needs to be further investigated because it relates to efforts to maintain their existence. This research was conducted using a qualitative-descriptive method based on the theory of Vera L. Zolberg and Howard S. Becker which explains how the construction of art is influenced by various supporting agents. Things that are a factor in efforts to maintain the existence of Formmisi-Yk are a sense of kinship, similar educational backgrounds, work competence, establishing good relationships and embracing generations who will continue Formmisi-Yk.